Do retailers set optimal prices in the case of the retail gasoline market?. (2015) - Kim, Daero; Davison, Matt; Ádegaard, Fredrik
How should gasoline retailers respond to other competing retailers and to changes in commodity gasoline prices to set their own prices over time? This question opens the door to an important discussion on price-setting strategies in the retail gasoline market. Retail gasoline price data, both panel and time series, is of great interest in the economic arena since it allows the testing of many theories about price formation, oligopolistic pricing, and consumer search. In this study, we present results from a unique new dataset, including daily sales, cost, and price data from 100 retail gasoline stations in a western European country. With this data, we empirically test various economic models to confirm, in full or in part, some earlier results based on North American data. We discuss a special case in which we empirically fit a model where retailers set prices partly in response to local competitors' prices.